O preceptor na residência em terapia intensiva: competências na formação do enfermeiro. - Costa, Simone Teixeira da Luz (2017)
The Residence is defined as a modality of postgraduate education. Courses in the Nursing Residency format have been offered in Brazil since the 1970s. In 1973, the UFBA School of Nursing elaborates the 1st Specialization in Residence format. The formation body of the Residence consists of preceptors hired by the institution for the purpose of guidance and follow-up of the residents in practical field. In this context the objective of this research is to investigate the competences of the preceptor for the training practice of the nurse practitioner who works in the Intensive Care Residency. The methodology used was the field research with a qualitative, exploratory and descriptive approach. The research was carried out in a Private Hospital, located in the City of Salvador that provides field of practice of the Residency Program in Intensive Care Nursing. The Intensive Care Unit has 30 beds. This research had 14 responders Nursing Preceptors, considering the inclusion and exclusion criteria. As a data collection instrument was used the semi structured interview directed to Nursing Preceptors. The pre-test was performed to validate the data collection instrument, with 3 randomly chosen nursing preceptors. Qualitative data were analyzed through the content analysis described by Franco (2012). After transcription, we opted to analyze the data using the Content Analysis technique, called Thematic Analysis. There were two thematic centers (Nursing Preceptor Competencies in Intensive Care Residency and Nursing Preceptors Perception in Intensive Care Residents training), and emerged the following categories (supervision, orientation, teaching, need for didactic-pedagogical training, Characteristics of the preceptor and teaching in the preceptory). It is concluded that the competences elect by the preceptory that determine their activity of supervision, orientation and teaching, and the perception of these, as well as the difficulties found in the practice with regard to the necessity of didactic-pedagogical technique, Inherent characteristics to the nurse practitioner in the practical field and the perception as a teacher in the preceptory, even if it is not compatible with the concepts of the great authors.